158 NT-pro BNP and Survival in Aortic Stenosis. (3rd June 2016) - Malley, Tamir; Vassiliou, Vassilis; Auger, Dominique; Raphael, Claire; Berry, Helen; Nyktari, Eva; Alpendurada, Francisco; Donovan, Jackie; Pennell, Dudley; Prasad, Sanjay
Abstract : Introduction: Elevated NT-pro BNP is associated with worse outcome in patients with cardiomyopathy. Hypothesis: We hypothesized that a mild elevation in NT-pro BNP may be associated with a worse outcome in patients with Aortic Stenosis (AS). Methods: Between 2011 and 2015, consecutive consenting patients with moderate (1.0–1.5 cm 2 ) or severe (<1 cm 2 ) AS considered for aortic valve intervention (either for severe AS or moderate AS with coronary disease) who had a cardiovascular magnetic resonance (CMR) scan undertaken for anatomy and function and also had blood stored for biomarker analysis were included. NT-pro BNP was measured using one-step immunoassay sandwich method with a final fluorescent detection (ELFA). Survival was obtained from hospital notes, electronic records and the National Strategic Office. Results: 112 patients (76 ± 10 years, 78 male) were included. The group was dichotomised according to NT-pro BNP value, into normal NT-pro BNP value group (values from 0–300 pg/ml, 23 patients) and high group (>300 pg/ml, 89 patients). End point was all cause mortality. At a median of 12 months follow-up, 21 patients had died, all from the high NT-pro BNP group. The high NT-pro BNP group had significantly worse prognosis hazard ratio=3.6 (95% CI=1.24–10.44, p = 0.00184). Although the NT-pro BNP correlated with LVEF its association with outcome was independent of this. Conclusions: In a prospective mixed cohort of patients with AS undergoing investigations for consideration of aortic valve intervention, even a mild elevation in NT-pro BNP is associated with worse short term outcome. This can be taken into consideration regarding timing of intervention especially in the asymptomatic population.